Cover film and image display device including the same

KR103032076B1Inactive Publication Date: 2026-10-13LG DISPLAY CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020230067618
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-25
Publication Date
2026-10-13
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 112023058173924-PAT00001
    Figure 112023058173924-PAT00001
  • Figure 112023058173924-PAT00002
    Figure 112023058173924-PAT00002
  • Figure 112023058173924-PAT00003
    Figure 112023058173924-PAT00003
Patent Text Reader

Abstract

The objective of the present invention is to provide a cover film having excellent scratch resistance, mechanical properties, and optical properties, as well as excellent elasticity, and an image display device including said cover film. A cover film according to the present invention is a cover film having a substrate layer and a surface layer chemically bonded to the substrate layer, wherein the surface layer comprises a polyurethane resin (X1) having urethane units, urea units, and polyorganosiloxane groups within the molecule, and the polyurethane resin (X1) is a reaction product of an active hydrogen component (A1) containing a compound (a1-1) and a non-yellowing type isocyanate component (B1), and the substrate layer comprises a polyurethane resin (X2) having urethane units within the molecule, and the polyurethane resin (X2) is a reaction product of an active hydrogen component (A2) not containing a compound (a1-1) and a non-yellowing type isocyanate component (B2), and has a specific crosslinking point concentration and a specific elastic recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a cover film and an image display device including the same. Background Technology

[0003] Recently, in addition to image display devices having flexibility (bendable, foldable, or rollable) as portable image display devices such as smartphones or tablet PCs, the development of image display devices having stretchability is underway (Patent Documents 1, 2, etc.).

[0004] Image display devices are equipped with a cover window to protect image display elements such as organic EL displays, LED displays, and liquid crystal displays. Currently, many portable image display devices use a cover window that includes a glass substrate. However, glass substrates are prone to breaking due to external impact and lack flexibility, so they cannot be applied to image display devices with flexibility (hereinafter referred to as "flexible displays") or image display devices with stretchability (hereinafter referred to as "stretchable displays"). Therefore, replacing glass substrates with resin films (cover films) is being considered, and image display devices using a transparent polyimide-based film as a cover film are known.

[0005] When a cover film is used as a surface protective material for an image display device, it is necessary to possess appropriate lubricity (scratch resistance) and mechanical properties (hardness) in addition to transparency. Furthermore, for cover films of flexible displays, it is preferable to have greater flexibility when the radius of curvature is small. On the other hand, when used as a cover film for a stretchable display, it is also necessary to have excellent elasticity. Conventional polyimide-based films lack elasticity, making it difficult to apply them to stretchable displays. Regarding these challenges, for example, Patent Document 3 describes using an elastic elastomer as a cover film.

[0006] However, there is a problem in that the stretchable cover film does not have sufficient scratch resistance. Although a method of coating a hardcoat layer with a lubricating material to improve scratch resistance is known, this method also cannot satisfy the scratch resistance required for the aforementioned flexible or stretchable displays. In addition, there is a problem that cracks occur in the film when the image display device is stretched. Furthermore, the method of applying a coating to the surface of the film also gives rise to new challenges, such as coating properties and adhesion to the film to be used as a substrate. Prior art literature

[0008] Patent Document 1: Japanese Patent Publication No. 2015-152922 Patent Document 2: Japanese Patent Publication No. 2020-102065 Patent Document 3: Japanese Patent Publication No. 2020-042981 The problem to be solved

[0009] Accordingly, the present invention aims to provide a cover film having excellent scratch resistance, mechanical properties, and optical properties, as well as excellent elasticity, and an image display device including said cover film. means of solving the problem

[0011] The inventors of the present application, after careful examination, discovered that a cover film and an image display device capable of solving all the aforementioned problems can be obtained by configuring the surface layer and the substrate layer as having a chemically bonded structure, wherein the surface layer and the substrate layer contain a specific polyurethane resin, and the polyurethane resin contained in the surface layer has a urea unit and a polyorganosiloxane group, and the polyurethane resin contained in the substrate layer has a specific crosslinking point concentration. This led to the completion of the present invention.

[0012] That is, the present invention has the following aspects.

[0013] [1] A cover film having a substrate layer and a surface layer located on at least one side of the substrate layer, wherein the substrate layer and the surface layer are chemically bonded, and the surface layer comprises a polyurethane resin (X1) having urethane units, urea units, and polyorganosiloxane groups in its molecule, wherein the polyurethane resin (X1) is a reaction product of an active hydrogen component (A1) and a non-yellowing type isocyanate component (B1), wherein the active hydrogen component (A1) comprises a compound (a1-1) comprising polyorganosiloxane groups and active hydrogen groups, and the ratio of the compound (a1-1) to the total amount (100 wt%) of the active hydrogen component (A1) and the non-yellowing type isocyanate component (B1) is 4.0 wt% or less, and the substrate layer comprises a polyurethane resin (X2) having urethane units in its molecule, wherein the polyurethane resin (X2) does not contain the compound (a1-1). A cover film that is a reaction product of an active hydrogen component (A2) and a non-yellowing type isocyanate component (B2), wherein the crosslinking point concentration of the polyurethane resin (X2) calculated from the following formula (1) is 0.4 mmol / g or more, and the elastic recovery rate when stretched by 100% is 80 to 100%.

[0014] Crosslinking point concentration (mmol / g) = (F-2) * (mol number of constituent monomers with 3 or more functions in 1g of the above polyurethane resin (X2)) … (1)

[0015] (In formula (1), F represents the number of functional groups of the constituent monomers with three or more functions.)

[0016] [2] In [1], the active hydrogen component (A1) is a cover film comprising at least one of a hydroxyl group, an amino group, and a carboxyl group as an active hydrogen group.

[0017] [3] A cover film according to [1] or [2], wherein the surface layer and the substrate layer comprise an environmental stabilizer, and the ratio of the environmental stabilizer in the surface layer and the substrate layer is 0.5 to 5.0 wt% each.

[0018] [4] In any one of [1] to [3], the non-yellowing type isocyanate component (B1) is a cover film comprising an isocyanate compound (b1) with three or more functions.

[0019] [5] A cover film in any one of [1] to [4], wherein the thickness of the surface layer is 10 μm or less and the thickness of the substrate layer is 150 μm or more.

[0020] [6] A cover film having a total light transmittance of 85% or more and a haze value of 5% or less when the cover film is stretched by 50% in any one of [1] to [5].

[0021] [7] A cover film in which the hysteresis loss rate of the cover film measured according to JIS K 6400-2 is 12% or less, in any one of [1] to [6].

[0022] [8] In [1], the above non-yellowing type isocyanate component (B1) is a cover film that is a polyisocyanate compound that does not contain aromatic components.

[0023] [9] [1] In the cover film, the chemical bonding between the substrate layer and the surface layer is formed through a reaction between the components in the substrate layer and the components in the surface layer at the interface between the substrate layer and the surface layer.

[0024]

[10] An image display device having a cover film described in any one of [1] to [9], an image display element, and a stretchable substrate or a flexible substrate stacked in order.

[0025]

[11]

[10] A display device having flexibility and / or elasticity. Effects of the invention

[0027] According to the present invention, a cover film having excellent scratch resistance, mechanical properties, and optical properties, as well as excellent elasticity, and an image display device including said cover film can be provided. Specific details for implementing the invention

[0029] Hereinafter, an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiments and may be implemented with appropriate modifications within a range that does not impede the effects of the present invention.

[0030] In this specification, the notation '~' means 'more than or equal to'.

[0031] [Cover Film]

[0032] A cover film according to the present embodiment has a substrate layer and a surface layer installed on at least one side of the substrate layer, wherein the substrate layer and the surface layer are chemically bonded, and the surface layer comprises a polyurethane resin (X1, a first polyurethane resin) having urethane bonds (or units), urea bonds, and polyorganosiloxane groups within its molecule, wherein the polyurethane resin (X1) is a reaction product of an active hydrogen component (A1, a first active hydrogen component) and a non-yellowing type isocyanate component (B1, a first non-yellowing type isocyanate component), wherein the active hydrogen component (A1) comprises a compound (a1-1) comprising polyorganosiloxane groups and active hydrogen groups, and the ratio of the compound (a1-1) to the total amount (100 wt%) of the active hydrogen component (A1) and the isocyanate component (B1) is 4.0 wt% or less, and the substrate layer comprises urethane within its molecule A cover film comprising a polyurethane resin (X2, second polyurethane resin) having a bond, wherein the polyurethane resin (X2) is a reaction product of an active hydrogen component (A2, second active hydrogen component) that does not contain the compound (a1-1) and a non-yellowing type isocyanate component (B2, second non-yellowing type isocyanate component), wherein the crosslinking point concentration of the polyurethane resin (X2) calculated from the following formula (1) is 0.4 mmol / g or more, and the elastic recovery rate when stretched by 100% is 80 to 100%.

[0033] Crosslinking point concentration (mmol / g) = (F-2) * (mol number of constituent monomers with three or more functions in 1g of polyurethane resin) … (1)

[0034] The cover film according to the present embodiment has excellent scratch resistance, mechanical properties, and optical properties, while also having excellent elasticity. The cover film according to the present invention will be described in detail below.

[0035] Surface layer

[0036] The cover film according to the present embodiment has a substrate layer and a surface layer installed on at least one side of the substrate layer. The surface layer comprises a polyurethane resin (X1) having urethane bonds, urea bonds, and polyorganosiloxane groups within its molecule. The surface layer is chemically bonded to the substrate layer described below. Here, "chemically bonded" means that the components constituting the surface layer and the components constituting the substrate layer react with each other and are chemically connected at the interface. By having such a configuration, interlayer delamination becomes difficult when stress is applied. As a result, scratch resistance and mechanical properties are improved. In addition, by including a polyurethane resin (X1) containing urethane bonds and urea bonds within its molecule, the scratch resistance of the surface layer is improved, and at the same time, appropriate hardness can be exhibited.

[0037] (Polyurethane resin (X1))

[0038] The polyurethane resin (X1) included in the surface layer is a reaction product of an active hydrogen component (A1, hereinafter referred to as component (A1)) and a non-yellowing type isocyanate component (B1, hereinafter referred to as component (B1)). In this specification, "non-yellowing type isocyanate" means an isocyanate compound that does not contain an aromatic component.

[0039] Component (A1) comprises a compound (a1-1) containing polyorganosiloxane groups and active hydrogen groups. The ratio of compound (a1-1) to the total amount (100 wt%) of component (A1) and component (B1) is 4.0 wt% or less. Scratch resistance and mechanical properties are improved by including a polyurethane resin (X1) in the surface layer.

[0040] [Active Hydrogen Component (A1)]

[0041] The active hydrogen component (A1) comprises a compound (a1-1, hereinafter referred to as compound (a1-1)) that includes a polyorganosiloxane group and an active hydrogen group as an essential component.

[0042] <Compound (a1-1)>

[0043] Compound (a1-1) is a compound having a polyorganosiloxane group and an active hydrogen group. By making the reaction product of component (A1) containing compound (a1-1) and component (B1) into a surface layer, the scratch resistance of the surface layer is improved.

[0044] The active hydrogen group included in compound (a1-1) may include at least one selected from hydroxyl groups, amino groups, and carboxyl groups, and it is preferable to include an amino group. By including an amino group in compound (a1-1), it becomes easier to obtain a polyurethane resin (X1) containing urea bonds within the molecule. Additionally, urea bonds in the polyurethane resin (X1) can be formed by the reaction of component (A1), excluding compound (a1-1), and component (B1).

[0045] The polyorganosiloxane group of compound (a1-1) may have a structure represented by the following general formula (I).

[0046] [General Formula(I)]

[0047]

[0048] R in general formula (Ⅰ) 1 ~ R 6 Each represents an alkyl group having a linear chain structure or a branched chain structure with 1 to 6 carbon atoms independently, and n represents an integer from 1 to 100.

[0049] For example, linear chain structures having 1 to 6 carbon atoms can be selected from methyl, ethyl, and n-propyl. Among these, in terms of the ease with which the mechanical properties of the surface layer can be improved, R 1 ~ R 6Each is preferably an alkyl group having 1 to 3 carbon atoms independently, and more preferably a methyl group. In addition, from the view that the mechanical properties of the surface layer and the haze value of the cover film are easily improved, n is preferably an integer from 10 to 70, and more preferably an integer from 15 to 50.

[0050] It is preferable that the compound (a1-1) has a polyorganosiloxane group represented by the general formula (I) above, and at least one active hydrogen group selected from one end, both ends, and the side chain of the molecular chain. Furthermore, it is more preferable that the compound (a1-1) has a hydroxyl group or an amino group selected from one end and both ends of the molecular chain. Commercial products may be used as such a compound (a1-1).

[0051] Commercial products of compounds (a1-1) having amino groups at both ends include, for example, Shin-Etsu Chemical Co., Ltd. products 'KF-8010' (functional group equivalent 430 g / mol), 'X-22-161A' (functional group equivalent 800 g / mol), 'X-22-161B' (functional group equivalent 1,500 g / mol), 'KF-8012' (functional group equivalent 2,200 g / mol), 'KF-8008' (functional group equivalent 5,700 g / mol), 'X-22-9409' (functional group equivalent 700 g / mol), and 'X-22-1660B-3' (functional group equivalent 2,200 g / mol) (all product names); Toray Dow Corning Co., Ltd. Examples include the products 'BY-16-853U' (functional group equivalent 460 g / mol), 'BY-16-853' (functional group equivalent 650 g / mol), and 'BY-16-853B' (functional group equivalent 2,200 g / mol) (all product names). One of these may be used alone, or two or more may be used in combination.

[0052] Examples of commercially available compounds (a1-1) having hydroxyl groups at both ends include ‘KF-6001’ (functional group equivalent 900 g / mol), ‘KF-6002’ (functional group equivalent 1,600 g / mol), ‘KF-6003’ (functional group equivalent 2,550 g / mol), and ‘X-22-4952’ (functional group equivalent 1,100 g / mol) from Shin-Etsu Chemical Co., Ltd. (all product names); and ‘SF8427’ (functional group equivalent 930 g / mol) from Toray Dow Corning Co., Ltd. (product name). These may be used individually or in combination of two or more.

[0053] Examples of commercially available compounds (a1-1) having a hydroxyl group at one end include 'X-22-170BX' (functional group equivalent 2,800 g / mol), 'X-22-170DX' (functional group equivalent 4,670 g / mol), 'X-22-176DX' (functional group equivalent 1,600 g / mol), and 'X-22-176F' (functional group equivalent 6,300 g / mol) (all product names) from Shin-Etsu Chemical Co., Ltd. These can be used individually or in combination of two or more types.

[0054] Among the commercially available products described above, X-22-161A, BY-16-853U, and KF-8012 are preferred as compounds (a1-1), and BY-16-853U and KF-8012 are more preferred.

[0055] The proportion of compound (a1-1) in the polyurethane resin (X1) is 4.0 wt% or less with respect to the total amount (100 wt%) of component (A1) and component (B1), preferably 1.0 to 3.0 wt%, and more preferably 1.5 to 2.0 wt%. If the proportion of compound (a1-1) in the polyurethane resin (X1) is 4.0 wt% or less, the scratch resistance and optical properties of the cover film can be achieved.

[0056] In conventional cover films described in Patent Document 3, etc., a method of applying a coating to a hard coat layer is used to improve the scratch resistance of the film. While coating the hard coat layer improves film hardness and scratch resistance, it reduces the elasticity of the film. Therefore, conventional cover films are difficult to apply to stretchable displays. The inventors focused on the lubricity rather than the hardness of the cover film and, as a result of their investigation, discovered that by incorporating a certain amount of a specific compound (a1-1) into the surface layer of the cover film, a resin that is slightly hard while having excellent lubricity and elasticity can be obtained. Furthermore, they discovered that by using a resin with a high crosslinking point concentration, described later, as the base layer and forming a layer structure in which the base layer and the surface layer are chemically bonded, the pencil hardness also increases due to the lubricity of the surface layer and the recovery power (recovery power) of the base layer.

[0057] <Other active hydrogen components (a1-2)>

[0058] Component (A1) includes other active hydrogen components (a1-2, hereinafter referred to as component (a1-2)) other than compound (a1-1). As component (a1-2), at least one selected from polymer polyols, chain extenders, and reaction stoppers described in, for example, International Publication No. 2021 / 002342 may be included. Among these, from the perspective of scratch resistance, it is preferable to include a polymer polyol described in International Publication No. 2021 / 002342, and it is more preferable to include a polycarbonate polyol. In addition, at least one of water, 1,4-diol (e.g., 1,4-butanediol), etc. may be included as a chain extender. In addition, diethanolamine, etc. may be included as a reaction stopper.

[0059] The proportion of the polymer polyol in component (a1-2) may be 50 to 100 wt% with respect to the total mass of component (a1-2), or 70 to 100 wt%. If the proportion of the polymer polyol is within the above range, the scratch resistance is likely to be better.

[0060] The content of component (a1-2) in component (A1) can be adjusted within a range where the total amount of compound (a1-1) and component (a1-2) is 100 wt% of the total weight of component (A1).

[0061] [Non-yellowing type isocyanate component (B1)]

[0062] Component (B1) is an isocyanate compound that does not contain aromatic components. Component (B1) reacts with component (A1) to form urethane bonds and urea bonds. Component (B1) is a polyisocyanate compound having at least two isocyanate groups and not containing aromatic components. That is, component (B1) is at least one isocyanate compound selected from aliphatic polyisocyanates and alicyclic polyisocyanates.

[0063] Aliphatic polyisocyanates include, for example, ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (hereinafter referred to as HDI), dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethylcaproate, bis(2-isocyanatoethyl)fumarate, bis(2-isocyanatoethyl)carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate; aliphatic triisocyanates such as 1,6,11-undecaine triisocyanate; Examples include aliphatic polyisocyanates with three or more functions, such as modified products containing urethane groups, carbodiimide groups, allophanate groups, urea groups, biuret groups, uretdione groups, uretimine groups, isocyanurate groups, or oxazolidone groups of the above-mentioned aliphatic diisocyanates or aliphatic triisocyanates [e.g., allophanate modified HDI (e.g., Tosoh Corporation product, product name 'CORONATE (registered trademark)-2793'), isocyanurate modified HDI (e.g., Asahi Kasei Corporation product, product name 'DURANATE (registered trademark) TLA-100'), and biuret modified HDI (e.g., Asahi Kasei Corporation product, product name 'DURANATE 24A-100')]. One type of aliphatic polyisocyanate may be used alone, or two or more types may be used in combination.

[0064] Examples of alicyclic polyisocyanates include isophorone diisocyanate (hereinafter referred to as IPDI), 4,4'-dicyclohexylmethane diisocyanate (hereinafter referred to as hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, and 2,5- or 2,6-norbornene diisocyanate. Alicyclic polyisocyanates may be used alone or in combination of two or more types.

[0065] It is preferable that component (B1) includes an isocyanate compound with three or more functions (b1, hereinafter referred to as compound (b1)), more preferable that it includes an allophanate-modified HDI or a biuret-modified HDI, and even more preferable that it includes an allophanate-modified HDI. By including compound (b1), it becomes easier to obtain a surface layer with superior heat resistance. As a result, it becomes easier to suppress film adhesion or sticking at high temperatures in a flexible display or stretchable display to which a cover film according to the present embodiment is applied. In particular, it becomes easier to suppress film adhesion to film when these displays are folded or rolled up.

[0066] The content of compound (b1) in component (B1) is more preferably 0.5 to 10 wt% with respect to the total mass of component (B1), more preferably 0.5 to 7.5 wt%, and even more preferably 0.5 to 5.0 wt%.

[0067] The proportion of component (B1) in the polyurethane resin (X1) is not particularly limited as long as it has the effect of the present invention. In one embodiment, the molar ratio (total amount of NCO groups / total amount of active hydrogen groups) between the total amount of NCO groups in component (B1) and the total amount of active hydrogen groups in component (A1) is preferably in the range of 1.00 to 1.10, and more preferably in the range of 1.00 to 1.05. If the molar ratio is in the range of 1.00 to 1.10, the scratch resistance is likely to be good.

[0068] The crosslinking point concentration of the polyurethane resin (X1) calculated from the following formula (1) is preferably 0.02 to 0.10 mmol / g and more preferably 0.04 to 0.08 mmol / g. The crosslinking point concentration of the polyurethane resin (X1) may be smaller than the crosslinking point concentration of the polyurethane resin (X2). If the crosslinking point concentration is within the above range, the scratch resistance is likely to be good.

[0069] Crosslinking point concentration (mmol / g) = (F-2) * (mol number of constituent monomers with three or more functions in 1g of polyurethane resin) … (1)

[0070] (In formula (1), F represents the number of functional groups of the constituent monomers with three or more functions.)

[0071] The total concentration of urethane bonds and urea bonds in the polyurethane resin (X1) is preferably 1.6 to 2.4 mmol / g and more preferably 1.8 to 2.2 mmol / g. If the total concentration of urethane bonds and urea bonds is within the above range, the scratch resistance is likely to be good. In addition, the total concentration of urethane bonds and urea bonds in the polyurethane resin (X1) can be calculated from the amount of raw materials of the active hydrogen component (A1) and the non-yellowing type isocyanate component (B1).

[0072] (Method for manufacturing polyurethane resin (X1))

[0073] The method for manufacturing the polyurethane resin (X1) according to the present embodiment is not particularly limited and may include a method (1) of obtaining a polyurethane resin (X1) by using a component (A1), a component (B1), and an organic solvent as needed to obtain a urethane prepolymer, and then reacting the urethane prepolymer with, for example, a chain extender, and a method (2) of obtaining a polyurethane resin (X1) by preparing the component (A1), the component (B1), and an organic solvent as needed in batches in a batch reaction vessel and reacting them by heating.

[0074] Detailed information regarding methods (1) and (2) can be found, for example, in the contents of International Publication No. 2021 / 002342.

[0075] The elastic recovery rate when the polyurethane resin (X1) is stretched by 100%, measured by the method described below, is preferably 40 to 100% and more preferably 50 to 100%. If the elastic recovery rate when the polyurethane resin (X1) is stretched by 100% is within the above range, the scratch resistance is likely to be good.

[0076] (Other components (C1))

[0077] The surface layer may include other components (C1, hereinafter referred to as component (C1)) other than the polyurethane resin (X1). Examples of components (C1) include antioxidants, environmental stabilizers such as UV absorbers and light stabilizers, plasticizers, adsorbents, fillers, release agents, and flame retardants. These may be used individually or in combination of two or more types.

[0078] Among these, it is preferable to include an environmental stabilizer as component (C1) from the perspective of easily suppressing the deterioration (discoloration, etc.) of the cover film over time while simultaneously improving light resistance and heat resistance.

[0079] Environmental stabilizers include, as mentioned above, antioxidants, ultraviolet absorbers, and light stabilizers.

[0080] Examples of antioxidants include hindered phenol compounds such as pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate; phosphorus compounds such as tris(2,4-di-t-butylphenyl)phosphite; and sulfur compounds such as pentaerythrityl-tetrakis(3-laurylthiopropionate), dilauryl-3,3'-thiodipropionate, pentaerythrityl-tetrakis(3-laurylthiopropionate), and dilauryl-3,3'-thiodipropionate. These may be used individually or in combination of two or more.

[0081] Examples of ultraviolet absorbers include benzotriazole compounds such as 2-(3,5-di-t-amyl-2-hydroxyphenyl)benzotriazole and 2-(5-methyl-2-hydroxyphenyl)benzotriazole.

[0082] Examples of light stabilizers include hindered amine compounds such as (bis-2, 2, 6, 6-tetramethyl-4-piperidyl)sebacate.

[0083] The surface layer may include one or more of the aforementioned environmental stabilizers. The content of the environmental stabilizer in the surface layer is preferably 0.5 to 5.0 wt% relative to the total mass of the resin composition constituting the surface layer, more preferably 1.0 to 5.0 wt%, and even more preferably 1.5 to 5.0 wt%. By having an environmental stabilizer content of 0.5 wt% or more in the surface layer, it becomes easier to obtain a cover film with minimal deterioration over time. Additionally, by having an environmental stabilizer content of 5.0 wt% or less in the surface layer, it becomes easier to obtain a cover film with excellent light resistance and heat resistance while suppressing yellowing of the film caused by the environmental stabilizer. Furthermore, when the surface layer is composed solely of the aforementioned polyurethane resin (X1), the content of the environmental stabilizer in the surface layer is a ratio to the total amount (100 wt%) of the polyurethane resin (X1) and the environmental stabilizer.

[0084] Other components other than environmental stabilizers included in the surface layer may include, for example, additives described in International Publication No. 2021 / 002342, used alone or in combination of two or more.

[0085] <Subject>

[0086] In the cover film according to the present embodiment, the substrate layer comprises a polyurethane resin (X2) having urethane bonds within the molecule. The polyurethane resin (X2) is a reaction product of an active hydrogen component (A2) that does not contain the compound (a1-1) and a non-yellowing type isocyanate component (B2), and is characterized by having a crosslinking point concentration of the polyurethane resin (X2) calculated from the following formula (1) of 0.4 mmol / g or more, and an elastic recovery rate of 80 to 100% when stretched by 100%. By including a polyurethane resin (X2) with an elastic recovery rate of 80 to 100%, the substrate layer becomes a soft layer with high resilience. As a result, the mechanical properties of the cover film, particularly pencil hardness, are improved.

[0087] (Polyurethane resin (X2))

[0088] The polyurethane resin (X2) included in the substrate layer is a reaction product of an active hydrogen component (A2, hereinafter referred to as component (A2)) that does not contain compound (a1-1) and a non-yellowing type isocyanate component (B2, hereinafter referred to as component (B2)). The crosslinking point concentration of the polyurethane resin (X2) calculated from the following formula (1) is 0.4 mmol / g or higher, preferably 0.4 to 0.6 mmol / g, and more preferably 0.4 to 0.5 mmol / g. If the crosslinking point concentration of the polyurethane resin (X2) calculated from formula (1) is 0.4 mmol / g or higher, the mechanical properties of the cover film, particularly pencil hardness, are improved.

[0089] Crosslinking point concentration (mmol / g) = (F-2) * (mol number of constituent monomers with three or more functions in 1g of polyurethane resin) … (1)

[0090] (In formula (1), F represents the number of functional groups of three or more constituent monomers in the polyurethane resin (X2).)

[0091] [Active hydrogen component (A2)]

[0092] Component (A2) does not contain compound (a1-1) and contains a polymer polyol (a2-1, hereinafter referred to as component (a2-1)) as an essential component.

[0093] The component (a2-1) is a polyol having a number average molecular weight (Mn) of 500 or more, preferably 500 to 5,000, more preferably 800 to 4,000, such as the polymer polyol described in International Publication No. 2021 / 002342. Among these, from the perspective of making it easy to adjust the crosslinking point concentration in the polyurethane resin (X2) to 0.4 mmol / g or more, the polymer polyol (a2-1) preferably comprises a polyol in which an alkylene oxide is added to a polyalcohol with 4 to 8 functions, such as pentaerythritol, sorbitol, mannitol, sorbitan, diglycerin, and dipentaerythritol, and it is more preferable to comprise a polyol in which an alkylene oxide is added to a polyalcohol with 6 to 8 functions, such as sorbitol, mannitol, sorbitan, and dipentaerythritol. Polymer polyol (a2-1) can be used alone or in combination with two or more types.

[0094] In addition, polyether polyols may be included as polymer polyols (a2-1). Examples of polyether polyols include compounds in which an alkylene oxide is added to a polyol having a number average molecular weight (Mn) or a formula weight of less than 500. One type of polyether polyol may be used alone, or two or more types may be used in combination.

[0095] In addition, the above alkylene oxide may include, for example, alkylene oxides having 2 to 12 carbon atoms, such as ethylene oxide, 1,2- or 1,3-propylene oxide, 1,2-, 1,3- or 2,3-butylene oxide, tetrahydrofuran, 3-methyl tetrahydrofuran, styrene oxide, α-olefin oxide, and epichlorohydrin. Among these, ethylene oxide and 1,2- or 1,3-propylene oxide are preferred from the perspective of scratch resistance.

[0096] In one embodiment, the polymer polyol (a2-1) may comprise a polyol to which at least one alkylene oxide selected from ethylene oxide, 1,2-propylene oxide, and 1,3-propylene oxide is added to at least one polyhydric alcohol selected from sorbitol, mannitol, sorbitan, and dipentaerythritol.

[0097] In one embodiment, the polymer polyol (a2-1) may comprise polytetramethylene ether glycol (PTMG) having Mn of 500 to 2,500.

[0098] The proportion of component (a2-1) in component (A2) is preferably 70 to 100 wt% with respect to the total mass of component (A2), more preferably 75 to 100 wt%, and even more preferably 75 to 90 wt%. If the proportion of the polymer polyol (a2-1) is within the above range, the scratch resistance is likely to be good.

[0099] In addition, 'Mn' in this specification can be measured by gel permeation chromatography, for example, under the following conditions.

[0100] Device: Waters Alliance 2695 (Waters product)

[0101] Column: One Guardcolumn Super HL, and one each of TSKgel SuperH2000, TSKgel SuperH3000, and TSKgel SuperH4000 (all Tosoh Corporation products) connected

[0102] Sample solution: 0.25 wt% THF solution

[0103] Solution injection volume: 10 μL

[0104] Flow rate: 0.6 mL / min

[0105] Measured temperature: 40 ℃

[0106] Detector: Refractive index detector

[0107] Reference material: Standard polyethylene glycol

[0108] <Other active hydrogen components (a2-2)>

[0109] Component (A2) may include other active hydrogen components (a2-2, hereinafter referred to as component (a2-2)) other than component (a2-1). As component (a2-2), at least one selected from chain extenders and reaction stoppers described in, for example, International Publication No. 2021 / 002342 may be included. Among these, it is preferable to include 1,4-butanediol or ethylene glycol for the sake of abrasion resistance, and it is more preferable to include 1,4-butanediol.

[0110] The proportion of 1,4-butanediol and / or ethylene glycol in component (a2-2) may be 50 to 100 wt% and 70 to 100 wt% with respect to the total mass of component (a2-2). If the proportion of 1,4-butanediol and / or ethylene glycol is within the above range, abrasion resistance is more likely to be improved.

[0111] [Non-yellowing type isocyanate component (B2)]

[0112] Component (B2) is an isocyanate compound that does not contain aromatic components. Component (B2) reacts with component (A2) to form a urethane bond. As for component (B2), the same polyisocyanate as component (B1) can be exemplified. Among these, for the sake of scratch resistance, component (B2) preferably contains HDI or IPDI. The content of HDI and IPDI in component (B2) is more preferably 80 to 100 wt% and more preferably 90 to 100 wt% with respect to the total mass of component (B2).

[0113] The proportion of component (B2) in the polyurethane resin (X2) is not particularly limited as long as it has the effect of the present invention. In one embodiment, the molar ratio of the total amount of NCO groups in component (B2) to the total amount of active hydrogen groups in component (A2) (total molar amount of NCO groups in component (B2) / [total molar amount of active hydrogen groups in component (A2)]) is preferably in the range of 1.00 to 1.10, and more preferably in the range of 1.00 to 1.05. If the molar ratio is in the range of 1.00 to 1.10, the scratch resistance is likely to be good.

[0114] (Method for manufacturing polyurethane resin (X2))

[0115] The method of manufacturing the polyurethane resin (X2) according to the present embodiment is not particularly limited, and it can be manufactured in the same way as the polyurethane resin (X1), except that component (A2) and component (B2) are used.

[0116] The elastic recovery rate when the polyurethane resin (X2) is stretched 100%, as measured by the following method, is 80 to 100%. If the elastic recovery rate when the polyurethane resin (X2) is stretched 100% is within the above range, a substrate layer with high resilience is obtained, and the pencil hardness of the cover film is improved.

[0117] In this embodiment, the elastic recovery rate when stretched by 100% can be measured by the following method.

[0118] <Method for Measuring Elastic Recovery Rate When Stretched to 100%>

[0119] (1) A sheet with a film thickness of about 2 mm is prepared using polyurethane resin (X1) or polyurethane resin (X2). A long, narrow rectangular test specimen with a length of 100 mm x a width of 5 mm is cut from the sheet and marked with lines such that the distance between the lines is 50 mm.

[0120] (2) The test specimen is set in the jig of an Instron type tensile testing machine (product of Shimadzu Corporation, product name 'Autograph'), and the test specimen is stretched at a constant speed of 500 mm / min under a 25°C atmosphere until the distance between the marks reaches 100%, and then immediately the test specimen is returned to the distance between the marks before stretching at the same speed.

[0121] (3) When performing this operation, the stress (M1) when 50% elongated during the elongation process and the stress (M2) when 50% elongated during the return process are measured, and the elastic recovery rate is calculated from the following equation (2).

[0122] Elastic recovery rate (%) = M2 / M1 * 100 … (1)

[0123] (Other components (C2))

[0124] The substrate layer may include other components (C2, hereinafter referred to as component (C2)) other than the polyurethane resin (X2). For example, the same as the aforementioned component (C1) may be exemplified as component (C2). Among these, it is preferable to include an environmental stabilizer as component (C2) from the perspective of easily suppressing the deterioration (discoloration, etc.) of the cover film over time while simultaneously improving light resistance and heat resistance.

[0125] The content of the environmental stabilizer in the substrate layer is preferably 0.5 to 5.0 wt% with respect to the total mass of the resin composition constituting the substrate layer, more preferably 1.0 to 5.0 wt%, and even more preferably 1.5 to 5.0 wt%. By having the content of the environmental stabilizer in the substrate layer be 0.5 wt% or more, it becomes easier to obtain a cover film with minimal deterioration over time. Additionally, by having the content of the environmental stabilizer in the substrate layer be 5.0 wt% or less, it becomes easier to obtain a cover film with excellent light resistance and heat resistance while suppressing yellowing of the film caused by the environmental stabilizer. Furthermore, when the substrate layer is composed only of the aforementioned polyurethane resin (X2), the content of the environmental stabilizer in the substrate layer is a ratio to the total amount (100 wt%) of the polyurethane resin (X2) and the environmental stabilizer.

[0126] In one embodiment, the total amount of component (C1) and component (C2) included in the cover film may be 0.5 to 5.0 wt%, 1.0 to 5.0 wt%, or 1.5 to 5.0 wt% with respect to the total mass of the entire resin composition constituting the cover film. By keeping the total amount of component (C1) and component (C2) included in the cover film within the above range, it becomes easier to obtain a cover film that undergoes less deterioration over time.

[0127] [Method for manufacturing cover film]

[0128] The method of manufacturing a cover film according to the present embodiment is not particularly limited. In one preferred embodiment, for example, it can be manufactured by a method comprising preparing a prepolymer for a polyurethane resin (X1) and a prepolymer for a polyurethane resin (X2) (Process (i)), coating the prepolymer for the polyurethane resin (X1) onto a release film, etc., to form a surface layer having a predetermined film thickness (Process (ii)), and coating the prepolymer for the polyurethane resin (X2) onto the surface layer to form a substrate layer with a predetermined film thickness (Process (iii)). Hereinafter, a manufacturing method including the above processes (i) to (iii) will be described.

[0129] <Process (i)>

[0130] Process (i) is a process for preparing a prepolymer for polyurethane resin (X1) and a prepolymer for polyurethane resin (X2).

[0131] A prepolymer for a polyurethane resin (X1) is a compound having hydroxyl groups at its ends, and can be prepared by reacting a component (A1) containing compound (a1-1) and a component (B1) in an organic solvent as needed. The hydroxyl group value of the prepolymer for the polyurethane resin (X1) is preferably 2.5 to 10.0 mg KOH / g in the composition from which the solvent has been removed.

[0132] The prepolymer for the polyurethane resin (X2) is a compound having isocyanate groups at the ends, and can be prepared by reacting component (A2) and component (B2) in an organic solvent as needed. The amount of isocyanate residue in the prepolymer for the polyurethane resin (X2) is preferably 2.0 to 6.0% of the composition from which the solvent has been removed.

[0133] When manufacturing polyurethane resins (X1) and (X2), a catalyst may be included as needed to promote the reaction. Specific examples of catalysts include, for instance, organometallic compounds (dibutyltin dilaurate, dioctyltin dilaurate, bismuth carboxylate, bismuth alkoxide, and chelate compounds of bismuth with compounds having dicarbonyl groups), inorganic metal compounds (bismuth oxide, bismuth hydroxide, bismuth halides, etc.), tertiary amines (triethylamine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]-7-undecene, etc.) and the combined use of two or more of these.

[0134] When preparing a urethane prepolymer for a polyurethane resin (X1) or (X2), the reaction temperature may be 50 to 140 ℃ or 70 to 100 ℃. In addition, the reaction time may be 1 to 10 hours or 2 to 8 hours.

[0135] <Fairness (ii)>

[0136] Process (ii) is a surface layer formation process. In process (ii), a urethane prepolymer for a polyurethane resin (X1) or its organic solvent solution is mixed with, if necessary, the aforementioned polymer polyol, chain extender, etc. component (a1-2) and environmental stabilizer, etc. component (C1), and then coated (coated) onto a release film to form a surface layer with a predetermined film thickness. The thickness of the surface layer is preferably 10 μm or less from the perspective of scratch resistance and optical properties, and 3 to 8 μm is more preferable. Additionally, when an organic solvent solution of a prepolymer for a polyurethane resin (X1) is used, process (ii) may include a process of drying the organic solvent. The drying temperature may be 30 to 160 °C or 100 to 150 °C. The drying time may be 10 seconds to 5 minutes or 20 to 60 seconds.

[0137] <Process (iii)>

[0138] Process (iii) is a process for forming a substrate layer. In process (iii), a urethane prepolymer for polyurethane resin (X2) or an organic solvent solution thereof is mixed with, if necessary, a component such as a chain extender (a2-2) and a component such as an environmental stabilizer (C2), and then coated (coated) the mixture onto the surface layer obtained in process (ii) to form a substrate layer with a predetermined film thickness. Preferably, process (iii) is a process of coating (coating) the prepolymer for polyurethane resin (X2) or an organic solvent solution thereof onto the surface layer and then heat-curing it. The curing temperature may be 60 to 150 ℃ or 80 to 120 ℃. The curing time may be 1 to 8 hours or 2 to 6 hours.

[0139] In addition, when an organic solvent solution of a prepolymer for a polyurethane resin (X2) is used, process (iii) may include a process of drying the organic solvent. The drying process of the organic solvent may be performed together with the curing.

[0140] The thickness of the substrate layer is preferably 150 μm or more from the perspective of mechanical properties, and 150 to 450 μm is more preferable.

[0141] A cover film according to the present embodiment can be manufactured by a manufacturing method comprising the above processes (i) to (iii).

[0142] When the cover film according to the present embodiment is stretched by 50%, the total light transmittance is preferably 85% or higher, and more preferably 90% or higher. In addition, the haze value of the cover film is preferably 5% or lower, and more preferably 1% or lower. As described above, since the cover film is used as a surface protective material for an image display device, it needs to have excellent transparency. If the total light transmittance of the cover film when stretched by 50% is 90% or higher and the haze value is 1% or lower, the transparency of the cover film is unlikely to decrease even when the image display device equipped with the cover film according to the present embodiment is stretched or folded.

[0143] The hysteresis loss rate of the cover film according to the present embodiment, measured according to JIS K 6400-2, is preferably 12% or less, more preferably 10% or less, and even more preferably 8% or less. By having a hysteresis loss rate of 12% or less, the response and durability of the image display device equipped with the cover film according to the present embodiment are likely to be improved when deformed.

[0144] [Image display device]

[0145] The image display device according to the present embodiment is characterized by having the cover film, the image display element, and the stretchable substrate or flexible substrate stacked in sequence. Since the image display device according to the present embodiment has a cover film that is excellent in scratch resistance, mechanical properties, and optical properties, and also has excellent elasticity, it can be used as a flexible display and / or a stretchable display. That is, the image display device according to the present embodiment can have flexibility and / or elasticity.

[0146] Image display element

[0147] In this specification, the term "image display element" means having a display medium in which contrast, brightness, reflectance, transmittance, etc. change due to electrical or magnetic action. Examples of display elements include EL (electroluminescence) elements, LED chips (white LED chips, red LED chips, green LED chips, blue LED chips, etc.), liquid crystal elements, etc.

[0148] Flexible Substrate

[0149] In this specification, "flexible substrate" refers to a substrate capable of bending, folding, winding, etc. In one embodiment, the flexible substrate may be composed of resin materials such as polyimide, polyethylene terephthalate, polyethylene naphthalate, and polycarbonate, but is not limited thereto.

[0150] Stretchable substrate

[0151] In this specification, "stretchable substrate" refers to a substrate that can be stretched. In one embodiment, the stretchable substrate may be a silicone rubber such as polydimethylsiloxane; an elastomer such as polyurethane or PTFE (Polytetrafluoroethylene), but is not limited thereto.

[0152] Other Compositions

[0153] The image display device according to the present embodiment may be equipped with a touch panel or a sensor element.

[0154] [Method for manufacturing an image display device]

[0155] The image display device according to the present embodiment may include a process of directly attaching a cover film according to the present embodiment onto an image display element.

[0156] Examples

[0157] The present invention will be explained more specifically below with reference to examples, but the present invention is not limited by these examples.

[0158] The materials used in the examples and comparative examples are as follows.

[0159] [Polyurethane Resin (X1): PU-X1]

[0160] <Active Hydrogen Component (A1)>

[0161] (Compound (a1-1))

[0162] A compound having a polyorganosiloxane backbone and amino groups at both ends of the molecular chain (product name 'BY-16-853U' from Toray Dow Corning Co., Ltd. or product name 'KF-8012' from Shin-Etsu Chemical Co., Ltd.).

[0163] ( Component (a1-2))

[0164] Polymer polyol: Polycarbonate diol (Asahi Kasei Corporation product, product name 'DURANOL T4671').

[0165] Chain extender: 1,4-butanediol, water.

[0166] Reaction stopper: Diethanolamine.

[0167] <Non-yellowing type polyisocyanate component (B1)>

[0168] Cyclic polyisocyanate (hydrogenated MDI).

[0169] Compound (b1): Allophanate-modified HDI (Tosoh Corporation product, product name 'CORONATE-2793').

[0170] [Polyurethane Resin (X2): PU-X2]

[0171] <Active Hydrogen Component (A2)>

[0172] ( Component (a2-1))

[0173] Polytetramethylene ether glycol (Mitsubishi Chemical Corporation product, product name 'PTMG-2000', Mn=2,000).

[0174] Polytetramethylene ether glycol (Mitsubishi Chemical Corporation product, product name 'PTMG-1000', Mn=1,000).

[0175] Polyoxypropylene sorbitol ether (product of Sanyo Chemical Industries, Ltd., product name 'SANNIX (registered trademark) SP-750').

[0176] ( Component (a2-2))

[0177] Chain extender: 1,4-butanediol

[0178] <Non-yellowing type polyisocyanate component (B2)>

[0179] Hexamethylene diisocyanate

[0180] [PU-1]

[0181] Polyurethane resin obtained by reacting a subject containing the following lubricant with a curing agent.

[0182] Subject: A prepolymer having hydroxyl groups at the ends, which is a reaction product of a polyol containing a polycarbonate polyol and a polyisocyanate.

[0183] Lubricant: Silicone compound.

[0184] Curing agent: Polyisocyanate compound.

[0185] [PU-2]

[0186] Two-component curing type urethane resin.

[0187] [PU-3]

[0188] Polyurethane resin obtained by reacting a subject containing the following lubricant with a curing agent.

[0189] Subject: A prepolymer that is a reaction product of a polyol and a polyisocyanate and has a hydroxyl group at the terminal.

[0190] Lubricant: Silicone compound.

[0191] Curing agent: Polyisocyanate compound.

[0192] [PDMS]

[0193] A copolymer of polydimethylsiloxane obtained by reacting the following α agent and β agent in a 1:1 ratio (having siloxane bonds within the molecule).

[0194] α-agent: Vinyl group-containing polydimethylsiloxane containing a platinum catalyst.

[0195] β-agent: A composition comprising a vinyl group-containing polydimethylsiloxane, a crosslinking agent, and a reaction inhibitor.

[0196] [Component (C1)]

[0197] Environmental stabilizer: a mixture of a UV absorber (benzotriazole compound: BASF Japan Ltd. product, product name 'TINUVIN (registered trademark) 329'), an antioxidant (hindered phenol compound: BASF Japan Ltd. product, product name 'Irganox (registered trademark) 245'), and a light stabilizer (hindered amine compound: BASF Japan Ltd. product, product name 'TINUVIN 144') in a ratio of 1:4:16.

[0198] [Component (C2)]

[0199] Environmental stabilizer: a mixture of a UV absorber (benzotriazole compound: BASF Japan Ltd. product, product name 'TINUVIN 329'), an antioxidant (hindered phenol compound: BASF Japan Ltd. product, product name 'Irganox 245'), and a light stabilizer (hindered amine compound: BASF Japan Ltd. product, product name 'TINUVIN 144') in a ratio of 1:11:45.

[0200] Example 1

[0201] Component (C1) was added to an organic solvent solution of a prepolymer for a polyurethane resin (X1) and mixed, and then coated onto a release film to a thickness of 5 μm. Afterward, a semi-cured surface layer was formed by drying at 145°C for 5 minutes. Component (C2) was added to a prepolymer for a polyurethane resin (X2) and mixed, and then coated onto the surface layer to a total thickness of 400 μm. The base layer and the surface layer were cured by curing at 145°C for 2 hours and then curing at 80°C for 24 hours, thereby producing a cover film in which the base layer and the surface layer are chemically bonded. The composition of the polyurethane resin (X1: PU-X1) constituting the surface layer of the produced cover film and the composition of the polyurethane resin (X2: PU-X2) constituting the base layer are as described in Table 1. The ratio of compound (a1-1) to the total amount of component (A1) and component (B1) in PU-X1 was 1.75 wt%. In addition, the ratio of component (C1) and component (C2) in the surface layer and substrate layer is as shown in Table 2.

[0202] In addition, the elastic recovery rates of PU-X1 and PU-X2 when stretched to 100%, measured under the following conditions, were 63% for PU-X1 and 85% for PU-X2.

[0203] <Method for Measuring Elastic Recovery Rate When Stretched to 100%>

[0204] (1) A sheet with a film thickness of 2 mm was made using polyurethane resin (X1) or polyurethane resin (X2). A long rectangular test specimen measuring 100 mm in length and 5 mm in width was cut from the sheet and marked with lines such that the distance between the lines was 50 mm.

[0205] (2) The test specimen was set in the jig of an Instron type tensile testing machine (product of Shimadzu Corporation, product name 'Autograph'), and the test specimen was stretched at a constant speed of 500 mm / min under a 25°C atmosphere until the distance between the marks reached 100%, and then immediately returned to the distance between the marks before stretching at the same speed.

[0206] (3) When performing this operation, the stress (M1) when stretched by 50% during the stretching process and the stress (M2) when stretched by 50% during the return process were measured, and the elastic recovery rate was calculated from the following equation (2).

[0207] Elastic recovery rate (%) = M2 / M1 * 100 … (2)

[0208] The tack, tactile, optical properties, breakage properties, scratch resistance, mechanical properties, elasticity, and environmental properties (deterioration over time) of the cover film obtained in Example 1 were evaluated according to the following conditions. The results are shown in Table 2.

[0209] <Tackiness and Tactile Sensibility of Cover Film>

[0210] (Adhesive)

[0211] Tests were conducted based on ASTM D2979, and a surface tack of 0.01 N or less was considered acceptable.

[0212] (touch)

[0213] In a static friction measuring instrument (product of Trinity-Lab. Inc., product name 'TL201Tt'), a tactile contactor was slid over a 15 mm X 10 mm area on the surface layer side of the cover film with a load of 20 gf and a speed of 1 mm / s to measure the coefficient of dynamic friction and the coefficient of static friction, and evaluated according to the following evaluation criteria.

[0214] (metewand)

[0215] Pass: The coefficient of dynamic friction and the coefficient of static friction were less than or equal to the measured values ​​of backplate glass (Corning Incorporated product, product name 'Eagle XG' (registered trademark)).

[0216] Fail: The coefficient of dynamic friction and the coefficient of static friction exceeded the measured values ​​of the backplate glass (Corning Incorporated product, product name 'Eagle XG').

[0217] <Optical Properties: Measurement of Total Light Transmittance and Haze Value>

[0218] The total light transmittance and haze values ​​of the obtained cover film when stretched to 0% (unstretched), when stretched to 50%, and when released were measured using a spectrophotometer (Konica Minolta, Inc. product, product name 'CM3600A'). In addition, when stretched to 50%, the value measured was taken while maintaining the obtained cover film sample stretched 1.5 times. In addition, when released, the value measured was taken immediately after releasing the cover film after stretching to 50%.

[0219] <Fracture Characteristics: Measurement of Hysteresis and Hysteresis Loss Rate>

[0220] The hysteresis and hysteresis loss rate of the obtained cover film were measured according to JIS K 6400-2.

[0221] Scratch Resistance: Steel Wool Test

[0222] Steel wool #0000, pressure 75 gf / cm 2 The degree of wear of the cover film (presence or absence of scratches or driving marks) was evaluated by reciprocating the surface layer side of the cover film at a speed of 40 mm / s according to the following evaluation criteria. In addition, the number of reciprocating cycles below indicates the number of reciprocating cycles in which no scratches or driving marks occurred on the cover film.

[0223] (metewand)

[0224] S: The number of round trips is 1,000 or more.

[0225] A: The number of round trips is 500 or more and less than 1,000.

[0226] B: The number of round trips is 250 or more and less than 500.

[0227] C: The number of round trips is 50 or more and less than 250.

[0228] D: The number of round trips is less than 50.

[0229] <Machine Characteristics: Pencil Hardness>

[0230] A cover film was fixed onto a glass substrate, and a pencil lead was pressed firmly onto the surface layer with a load of 750 gf. In this state, the pencil was moved at a speed of 300 mm / min, and the scratch hardness of the cover film was evaluated as the hardness of the pencil lead. Additionally, the cover film was fixed onto the glass substrate without adhesive and the test was performed.

[0231] <Stretchability: Heat Resistance Test>

[0232] After overlapping the paper onto the cover film, the film was rolled up so that the paper adhered to the surface layer of the cover film and stored at 95°C for 300 hours. Afterward, it was cooled to room temperature to visually check for the adhesion of the paper to the surface layer of the cover film and evaluated according to the following evaluation criteria.

[0233] (metewand)

[0234] Pass: The paper did not peel off when the cover film was returned to its original shape, and the paper did not adhere to the surface layer of the cover film.

[0235] Fail: When returning the cover film to its original shape, the paper tore, while the paper remained attached to the surface layer of the cover film.

[0236] Comparative Examples 1 to 3

[0237] A cover film was prepared using the resin shown in Table 2. In addition, Comparative Example 1 was prepared using the same method as Example 1, except that the resin shown in Table 2 was used. Comparative Example 3 was prepared by mixing agent α and agent β in a 1:1 ratio, applying them onto a release film, and curing at 130°C for 5 minutes to produce a cover film (PDMS film) consisting only of a surface layer. Comparative Example 2 was prepared by performing corona discharge treatment on the PDMS film of Comparative Example 3, applying PU-3, and curing at 80°C for 1 hour to produce a cover film. For each cover film of the comparative example, tack, tactile properties, optical properties, breakage properties, scratch resistance, mechanical properties, and elasticity properties were evaluated according to the following conditions using the same method as in Example 1. The results are shown in Table 2.

[0238] Reference Example 1

[0239] For the cover film of Example 1, samples were prepared containing 0 wt% (not containing components (C1) and (C2)), 1.5 wt%, 3 wt%, and 5 wt% of the resin composition constituting each layer, with respect to the surface layer and substrate layer, and an environmental test was performed under the following conditions. As a result, the sample with 0 wt% had a Y1 (yellowing degree) exceeding 10 after several hours, and the film yellowed. On the other hand, in the sample containing 1.5 to 5 wt% of components (C1) and (C2), the Y1 was approximately 1.2 to 2.4, and no discoloration of the film occurred. From these results, it was confirmed that by incorporating a certain amount of components (C1) and (C2) (environmental stabilizers) into the surface layer and substrate layer, it becomes easier to suppress the deterioration of the cover film over time.

[0240] Environmental Test

[0241] Cover film sample at temperature 65 ℃, humidity 60 % RH, metal halide lamp 830 W / m² 2It was stored for 240 hours under the conditions. After storage, the Y1 (yellowing degree) of the cover film was measured using a spectrophotometer (Konica Minolta, Inc. product, product name 'CM3600A').

[0242] Table 1

[0243]

[0244] Table 2

[0245]

[0246] The '-' in Tables 1 and 2 indicates that the component (or the exemplified combination) is not included.

[0247] As shown in Table 2, the cover film of Example 1, which satisfies the configuration of the present embodiment, exhibited excellent scratch resistance, mechanical properties, and optical properties, while also having good stretchability. On the other hand, the cover films of Comparative Examples 1 to 3, which do not satisfy the configuration of the present embodiment, showed inferiority in any one of the scratch resistance, mechanical properties, optical properties, or stretchability. From the above results, it was confirmed that the cover film according to the present embodiment has excellent scratch resistance, mechanical properties, and optical properties, as well as excellent stretchability. Furthermore, in an image display device equipped with the cover film according to the present embodiment, the film does not break or rupture even when the device is stretched or folded.

Claims

Claim 1 A cover film having a substrate layer and a surface layer located on at least one side of the substrate layer, wherein the substrate layer and the surface layer are chemically bonded, and the surface layer comprises a polyurethane resin (X1) having urethane units, urea units, and polyorganosiloxane groups in its molecule, wherein the polyurethane resin (X1) is a reaction product of an active hydrogen component (A1) and a non-yellowing type isocyanate component (B1), wherein the active hydrogen component (A1) comprises a compound (a1-1) comprising polyorganosiloxane groups and active hydrogen groups, and the ratio of the compound (a1-1) to the total amount (100 wt%) of the active hydrogen component (A1) and the non-yellowing type isocyanate component (B1) is 4.0 wt% or less, and the substrate layer comprises a polyurethane resin (X2) having urethane units in its molecule, wherein the polyurethane resin (X2) comprises the compound A reaction product of an active hydrogen component (A2) that does not contain (a1-1) and a non-yellowing type isocyanate component (B2), wherein the crosslinking point concentration of the polyurethane resin (X1) calculated from the following formula (1) is 0.02 to 0.1 mmol / g, the crosslinking point concentration of the polyurethane resin (X2) calculated from the following formula (1) is 0.4 mmol / g or higher, and the elastic recovery rate when stretched by 100% is 80 to 100%, wherein the non-yellowing type isocyanate component (B1) comprises an isocyanate compound (b1) with three or more functions, and the non-yellowing type isocyanate component (B2) comprises a compound (b2) which is hexamethylene diisocyanate (HDI) or isophorone diisocyanate (IPDI), and the content of the isocyanate compound (b1) with three or more functions in the non-yellowing type isocyanate component (B1) is A cover film having a content of compound (b2) in the non-yellowing type isocyanate component (B2) within the range of 0.5~10 wt%, and a content of compound (b2) in the non-yellowing type isocyanate component (B2) within the range of 80~100 wt%.Crosslinking point concentration (mmol / g) = (F-2) * (mol number of constituent monomers with three or more functions in 1g of the above polyurethane resins (X1, X2)) … (1) (In Equation (1), F represents the number of functional groups of constituent monomers with three or more functions). Claim 2 A cover film according to claim 1, wherein the active hydrogen component (A1) comprises at least one of a hydroxyl group, an amino group, and a carboxyl group as an active hydrogen group. Claim 3 A cover film according to claim 1, wherein the surface layer and the substrate layer comprise an environmental stabilizer, and the ratio of the environmental stabilizer in the surface layer and the substrate layer is each 0.5 to 5.0 wt%. Claim 4 In claim 1, the non-yellowing type isocyanate component (B1) is a cover film comprising an isocyanate compound (b1) with three or more functions. Claim 5 A cover film according to claim 1, wherein the thickness of the surface layer is 10 μm or less and the thickness of the substrate layer is 150 μm or more. Claim 6 A cover film according to claim 1, wherein the total light transmittance of the cover film is 85% or more when stretched by 50%, and the haze value is 5% or less. Claim 7 A cover film according to claim 1, wherein the hysteresis loss rate of the cover film measured according to JIS K 6400-2 is 12% or less. Claim 8 In claim 1, the non-yellowing type isocyanate component (B1) is a cover film that is a polyisocyanate compound not containing an aromatic component. Claim 9 A cover film according to claim 1, wherein the chemical bonding between the substrate layer and the surface layer is formed through a reaction between a component within the substrate layer and a component within the surface layer at the interface between the substrate layer and the surface layer. Claim 10 An image display device comprising: a cover film described in any one of claims 1 to 9; an image display element located below the cover film; and a stretchable substrate or a flexible substrate located below the image display element. Claim 11 In claim 10, an image display device having flexibility and / or elasticity. Claim 12 delete

Citation Information

Patent Citations

  • Thermoplastic polyurethane resin and its manufacturing method

    JP2003026755A

  • Polyurethane laminated article and its manufacturing method, and sealing material and vibration-damping and shock-absorbing material using the same

    JP2009024060A

  • Polyurethane resin

    JP2013147614A

  • Polyurethane resin

    JP2015131871A

  • double-layer film

    KR1020210144781A